2017
DOI: 10.1002/ams2.281
|View full text |Cite
|
Sign up to set email alerts
|

Cardiocerebral and cardiopulmonary resuscitation – 2017 update

Abstract: Sudden cardiac arrest is a major public health problem in the industrialized nations of the world. Yet, in spite of recurrent updates of the guidelines for cardiopulmonary resuscitation and emergency cardiac care, many areas have suboptimal survival rates. Cardiocerebral resuscitation, a non‐guidelines approach to therapy of primary cardiac arrest based on our animal research, was instituted in Tucson (AZ, USA) in 2002 and subsequently adopted in other areas of the USA. Survival rates of patients with primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…As recommended by both Saudi Heart Association and American Heart Association, the single rescuer should begin CPR with 30 chest compressions followed by two breaths. [ 21 22 ] Although 66.7% of the participants knew the correct compression-ventilation ratio, a significant difference between the academic years has been recorded giving a higher prevalence among interns then followed by 3 rd , 5 th , and 4 th year.…”
Section: Discussionmentioning
confidence: 99%
“…As recommended by both Saudi Heart Association and American Heart Association, the single rescuer should begin CPR with 30 chest compressions followed by two breaths. [ 21 22 ] Although 66.7% of the participants knew the correct compression-ventilation ratio, a significant difference between the academic years has been recorded giving a higher prevalence among interns then followed by 3 rd , 5 th , and 4 th year.…”
Section: Discussionmentioning
confidence: 99%
“…In a swine model, Zuercher et al [ 34 ] showed that early IO adrenaline administration was superior to delayed IV adrenaline injection in achieving 24-h survival. Therefore, despite that the meta-analytic results demonstrated inconclusive or non-significant association between either vascular access with OHCA outcomes, emergency care providers should still take into account the influence of delay in medication administration on outcomes when they attempt to establish vascular access, especially for patients with non-shockable rhythms [ 35 ]. It should especially be emphasized that no relevant clinical outcome-directed studies were identified in current review for pediatric patients, whose vascular access was difficult to be obtained during CPR.…”
Section: Discussionmentioning
confidence: 99%
“…No active ventilation takes place during the first three cycles [6][7][8][9]. Compared with the pre-implementation period CCR was associated with improved neurologically intact survival of patients with OHCA in large US regions [10].…”
Section: Introductionmentioning
confidence: 98%